Application of Arbuscular Mycorrhizal Fungi and Manure to Improve Saline Soil Characteristics - Maghfirotun Ni'mah Hidayati; Rossyda Priyadarshini; Purnomo Edi Sasongko (The University of Lampung, 2026)
Soil salinity can damage soil structure due to its high sodium chloride content, leading to soil erosion and reduced aeration, which decreases the ability of plants to absorb water and inhibits plant growth. One approach to overcome this problem is by improving the chemical properties of saline soil; therefore, research on the application of arbuscular mycorrhizal fungi and manure is needed. This study aimed to determine whether the addition of manure and arbuscular mycorrhizal fungi at appropriate rates could improve the chemical properties of saline soil. A completely randomized design (CRD) with two factors was used, in which the first factor was the dose of arbuscular mycorrhizal fungi with four levels and the second factor was manure application with two levels, each repeated three times, resulting in eight treatments and 24 experimental units. The results showed that although the application of mycorrhizal fungi and manure did not significantly affect soil pH or electrical conductivity (EC), a single factor manure treatment increased soil pH and reduced EC values, while a single factor treatment of arbuscular mycorrhizal fungi reduced soil EC values. The combined application of manure and arbuscular mycorrhizal fungi significantly increased N-available (NH₄⁺ and NO₃⁻) during the first week after the application of 20 ton/ha of manure and 105 CFU/mL of arbuscular mycorrhizal fungi (M1K1).